Decoupling and decomposition analysis of investments and CO2 emissions in information and communication technology sector. (15th November 2021) - Wang, Jianda; Jiang, Qingzhe; Dong, Xiucheng; Dong, Kangyin
Highlights: Carbon mitigation effect of information and communication technology (ICT) investment is assessed. ICT investment has an ideal decoupling state with carbon intensity in most economies. Emission intensity of ICT investment contributes an increase of carbon emissions. Efficiency of ICT investment is most significant factor in inhibiting emissions. ICT industrial structure should be further improved in the post-pandemic era. Abstract: Organization of Economic Cooperation and Development (OECD) economies are facing a substantial increase in the information and communication technology (ICT) investments in the context of rapid spread of the Coronavirus Disease-2019 (COVID-2019) pandemic and constraints of emissions reduction. However, the mechanism of the impact of ICT investments on carbon dioxide is still unclear. Therefore, by employing the decoupling-factor model and Generalized Divisia Index Method, we explore the decoupling states of ICT investments and emission intensity, and the driving factors of ICT investments' scale, intensity, structure, and efficiency effects on carbon emissions in 20 OECD economies between 2000 and 2018. The results indicate that the number of economies with an ideal state of strong decoupling rose to nine between 2009 and 2018 compared to no economies between 2000 and 2009. The emission intensity of ICT investments contributes to a significant increase of carbon emissions, and the structure and efficiency of ICT investments always restrain the growth of carbon emissions. Significant emissions changes caused by the driving factors are shown in many economies before and after the crisis, reflecting the differences in the strategic choices of ICT investments and the impact on emissions due to the crisis such as the COVID-2019 pandemic. And policy implications for energy and carbon dioxide mitigation strategies in the post-COVID-2019 era are also provided.